APPLICATION OF HYDRO-REMOVAL ASH IN NON-AUTOCLAVED FOAM CONCRETE TECHNOLOGY - Ermukhanbet, M.A.; Saduakassov, M.S.; Lapin, V.A.; Tokmajeshvili, G.G.; Bayusupova, K.T. (GEOMATE Journal, 2025)
This study investigates the influence of various fillers and curing conditions on the strength development of foam concrete. It was found that conventional sand-based mixtures fail to achieve the required strength under both steaming and natural hardening conditions. Experimental results demonstrate that substituting sand with activated hydraulic ash, particularly when combined with a hardening accelerator, significantly improves the strength of non-autoclaved cellular concrete. The research also examines the effect of ash with different grinding fineness on the physical and mechanical properties of both autoclaved and non-autoclaved foam concrete. Since autoclaved curing ensures complete hydration, a comparative analysis was conducted using samples cured under atmospheric pressure in a steam chamber at 90 °C and those treated in an autoclave at 167 °C and 0.8 MPa. This approach enabled the identification of strength variations related to the content and reactivity of silicon dioxide in the ash. The novelty of this research lies in demonstrating the practical efficiency of using activated hydraulic removal ash combined with a chemical hardening accelerator to produce non-autoclaved cellular concrete with acceptable strength characteristics. The methodology emphasizes the comparative evaluation of identically composed mixtures subjected to different curing regimes, offering valuable insights into optimizing material composition and processing for sustainable and energy-efficient foam concrete production.